Clinical expert consensus on the assessment and protection of pancreatic islet β-cell function in type 2 diabetes mellitus. (March 2023) - Zhu, Jian; Han, Junfeng; Liu, Liehua; Liu, Yu; Xu, Wen; Li, Xiaomu; Yang, Lin; Gu, Yong; Tang, Wei; Shi, Yongquan; Ye, Shandong; Hua, Fei; et al.
Abstract: Islet β-cell dysfunction is a basic pathophysiological characteristic of type 2 diabetes mellitus (T2DM). Appropriate assessment of islet β-cell function is beneficial to better management of T2DM. Protecting islet β-cell function is vital to delay the progress of type 2 diabetes mellitus. Therefore, the Pancreatic Islet β-cell Expert Panel of the Chinese Diabetes Society and Endocrinology Society of Jiangsu Medical Association organized experts to draft the " Clinical expert consensus on the assessment and protection of pancreatic islet β-cell function in type 2 diabetes mellitus." This consensus suggests that β-cell function can be clinically assessed using blood glucose-based methods or methods that combine blood glucose and endogenous insulin or C-peptide levels. Some measures, including weight loss and early and sustained euglycemia control, could effectively protect islet β-cell function, and some newly developed drugs, such as Sodium-glucose cotransporter-2 inhibitor and Glucagon-like peptide-1 receptor agonists, could improve islet β-cell function, independent of glycemic control.